MIXED MODE CATIONIC EXCHANGE CHROMATOGRAPHY LIGANDS BASED ON SUBSTITUTED 2-BENZAMIDO ACETIC ACID STRUCTURES (2022)
The subject invention pertains to mixed mode chromatography ligands and chromatography matrices suitable for the purification of proteins from biological sources or biological samples. Methods of making chromatography matrices comprising the disclosed ligands and using the disclosed chromatography matrices are also provided.